Mushaf Al-Qurâan Nusantara: Perpaduan Islam dan Budaya Lokal - Lestari, Lenni (Jurnal At-Tibyan: Jurnal Ilmu Alquran dan Tafsir, 2016)
Crystalization of statement âAl-Qurâan will be protected all the timeâ has been totally convinced and created by any form. One of them is the tradition of Al-Qurâan writing and printing. Circumstancially, this phenomenon indicated the development of living Qurâan. This paper will discuss about the development of Mushaf Al-Qurâan of Indonesia, from the tradition of hand writing until digital era. Beside it, this paper will also analyze the phenomenon of Mushaf of Al-Qurâan in Indonesia, in the concept of living Qurâan, by reception of hermeneutic, aesthetic and cultural. This paper concludes; the development of writing and printing Al-Qurâan, includes hand writing and digitalization era, is the tradition has been always preserved by Indonesian people. As a kind of living Qurâan, the Mushaf of Indonesia is a evidence of the achievement of cultural transformation and a good civilization.